Comparison of Air-Conduction and Bone-Conduction Hearing Thresholds for Pure Tones and Octave-Band Filtered Sound Effects - Abouchacra, Kim S.; Letowski, Tomasz (Journal of the American Academy of Audiology, 1999)
The purpose of this study was to measure air-conduction (AC) and bone-conduction (BC) hearing thresholds with pure-tone and filtered sound effect stimuli using standard audiometric equipment. A group of 20 young, normal-hearing listeners participated in the study. Pure-tone stimuli were 250, 500, 1000, 2000, and 4000 Hz. Sound effect stimuli were 12 natural sounds that were spectrally limited to an octave bandwidth centered at either 250, 500,1000, 2000, or 4000 Hz. The AC and BC detection thresholds were measured using a clinical audiometer (Madsen Orbiter 922) with a B-71 bone oscillator and TDH-50 earphones. Results indicated that detection thresholds for the pure-tone and corresponding octave-band sound effect stimuli were within 3 to 4 dB of each other for both AC and BC testing. The findings support the notion that octave-filtered sound effects are a viable alternative to pure-tone stimuli for use in audiology clinics.
Keywords: Air- and bone-conduction thresholds; detection, sound effect stimuli